Exploring the Mind of God: An Introduction to Shiʿite Legal Epistemology - Bata, Hashim (Middle East and Islamic Studies E-Books Online, Collection 2023., 2023)
This book introduces readers to the legal epistemology that is advocated within Twelver Shiʿite uṣūl al-fiqh (legal theory). It critically surveys the epistemological underpinnings upheld by post-19th century Uṣūlī clerics that impel them to mainly deduce and interpret Sharia using scripture and literalist hermeneutical methods. An evaluation of these underpinnings uncovers the important juxtaposition that exists between the seminarian discourses of uṣūl al-fiqh and philosophy. The book hypothesises that uṣūl al-fiqh has both space and historical precedence to accept alternative epistemological theories that may enable orthodox Shiʿite clerics to display greater dynamism in deducing and interpreting Sharia.